Interaksi desa-kota pada kota-kota kecil di Kota Medan dan Kecamatan Percut Sei Tuan - Muhammad Anas Kautsar; Afitzka Al Zahwa; Citra Aulia; Lumban Gaol, Riski Fanni; Purba, Tondang Raja Pangihutan (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
This study examines the dynamics of interactions between villages and small towns in Medan City and Percut Sei Tuan Sub-district, North Sumatra. Rural-urban interactions are crucial in supporting sustainable regional development, especially in terms of population mobility, distribution of goods and services, and knowledge exchange. The approach used is gravity analysis and evaluation of spatial factors that influence the strength of inter-regional interactions. Secondary data from BPS and interactive maps were used to identify distribution patterns and intensity of relationships between villages and towns. The results show that villages with adequate infrastructure and high population, such as Tembung Village, have a very strong level of interaction with Medan City. The small town in this study serves as a node for trade and distribution of village products. However, there are challenges in the form of gaps in access to infrastructure, education and health between regions. The findings suggest the need for integrated planning that supports regional connectivity and village economic strengthening. This research provides an important basis for policy makers in designing more inclusive and equitable regional development strategies.